My war - Rooney, Andrew A. (New York : Times Books, 1995)
In 1939, Andrew A. Rooney was a pretty typical twenty-year-old college boy at Colgate University. He played football, was interested in philosophy, thought he wanted to be a writer (but has no idea how to go about becoming one), and felt the America Firsters made pretty good sense. When he read that Hitler had invaded Poland, his first thought was "Where is Brest-Litovsk?" followed quickly by "How can I get out of this?" But, like millions of other Americans in that remarkable time, Andy Rooney eventually found himself in basic training in North Carolina, learning to break down a rifle, launch an artillery round, and defend freedom and democracy. In short order, his unit, the 17th Field Artillery Regiment, was in England receiving further training and waiting for the Normandy invasion to begin. And that's where Andy Rooney's war really began.
Includes index.
Keywords: Rooney, Andrew A; World War, 1939-1945 -- Journalists -- Biography; World War, 1939-1945 -- Personal narratives, American